Menumbuhkan Jiwa Enterpreneur Berbasis Syariah Di Kalangan Generasi Muda - Shofiyah Shofiyah (Al-Musthofa: Journal of Sharia Economics, 2018)
Until now unemployment in Indonesia is still a very serious problem and very difficult to overcome. Government programs to reduce unemployment have not yet shown significant results. Therefore, all parties are expected to continue to think and innovate to realize real work in overcoming the gap between employment with graduates of educational institutions. Relating to the above is Islam as a religion perfect to give guidance to humans about various things including one of them is in the field of business with the aim that humans have the right guidelines in carrying out their business and in establishing work relations among others so that they provide mutual benefits and create prosperity and prosperity for all human beings. business people are not wrong in carrying out usahanaya, especially for the younger generation. Entrepreneurship is very important for oneself and also for others because entrepreneurship in addition to prospering itself also describes employment opportunities to other people in a right and lawful way, this automatically reduces unemployment while providing lessons for the next generation by developing sharia entrepreneurship .